ROLAND BARTHES' SEMIOTIC ANALYSIS ON JAMAL RAMADHAN'S PHOTOJOURNALISTIC WORKS ABOUT THE ARREST OF THE MINISTER OF AGRICULTURE - Sitompul, Qory Amalia Az-Zahra; Nasution, Kasron (Pena Cendekia Insani, 2025)
This study investigate the deep meaning contained in photo journalism about: “The arrest of the former Minister of Agriculture by the Corruption Eradication Committee, using Roland Barthes' semiotic approach”. The photo shows Syahrul Yasin Limpo wearing a KPK prisoner's vest in the middle of the crowd, not only present the visual fact of an arrest, but also include into cultural and ideological content. Through the analysis of denotation, connotation, and myth, this study reveal how the photo represent the issue about law, justice, power, and public attention. The research use a type of qualitative descriptive research that use Roland's semiotic analysis Barthes' research result show that a journalistic photo can become part of a complex social and cultural construction, where meaning not only lie in what is directly visible, but also in interpretation influenced by social, cultural context and the role of the media.